Efecto de un fertilizante orgánico en la producción de banano en el cantón Balao provincia del Guayas - Quezada Perez, Alexis Efren (2015)
At Hacienda Deli 5 Balao belonging to the canton of Guayas province; the effects of a fertilizer Hemozym NP5-30 applied to a template Williams banana variety was studied. In the trial optimum management staff of the variety Williams was recorded. The experimental product Homozym NP 5-30, the effect of nitrogen from amino acids and phosphorus exert an enhancing effect on plant growth, especially in the leaf area of the variety. Other agronomic characteristics of the variety that was experienced significant increases root mass, thus increasing the capacity of absorption of nutrients. Productivity indicators in which high statistical significance was obtained for treatments were bunch weight, number of hands, and the production of boxes ratio. As regards the dose, the low dose application of 2.0 l / ha weight led to increase twice compared to absolute control. Doses above 2.0 liters / ha produce regressive effects on plant productivity.